Analysis of the relationship between peak time of GR4J model and observed discharge: A case study of river basins (DAS) in Java Island - Munajat, C. M.; Darsono, Sri Legowo W.; Soekarno, Indratmo; Harlan, Dhemi (Edelweiss Applied Science and Technology, 2025)
This study aims to improve the accuracy of the GR4J model in simulating the transformation of rainfall into discharge in ten watersheds on Java Island, which are representative of tropical climate conditions in developing countries. This study involves collecting daily rainfall and evapotranspiration data as model inputs, as well as observed discharge data for calibration and validation. The calibration process focuses on minimizing the error between predicted and observed discharge using the Nash-Sutcliffe Efficiency (NSE) and Relative Volume Error (RVE) metrics. The main focus of this study is to adjust the peak time parameter (X4) to match the observed peak discharge time (Tp). The results of the analysis show a significant correlation between the X4 values obtained by the model and the observed Tp, which allows the development of an adjustment formula in the GR4J model equation. This adjustment improves the accuracy of the unit hydrograph simulation both in shape and magnitude, allowing the model to better reflect realistic flow conditions. This study concludes that by adjusting the peak time parameter, the GR4J model can be optimized to provide more accurate discharge predictions in watersheds on Java Island. This increase in accuracy is expected to support more effective water resource planning and management in other regions of Indonesia.